Pengembangan desain tas wanita berbahan rumput Purun menggunakan metode ATUMICS - Widya Christa Turang; Daniel Alexander Octavianus Turang (Institut Seni Indonesia Yogyakarta, 2021)
Purun is a wild plant that can be found in Kalimantan. Purun is used as material for making traditional handicraft products. Utilization of Purun is currently not favored in demand by the general public, because the design of Purun handicraft products is not yet fully developed so that it didn't get enough attention in the community. This study was conducted using the ATUMICS method with a rapid ethnographic approach and observation technique to support the data collection process and interview technique to explore the depth of the data. The purpose of this research is to develop designs from Purun-made products to increase the selling value of Purun-made products. Based on research that has been done, the design of Purun-made products will focus on women's fashion products in the form of women's bags. Women's handbag products are one of the pioneers of fashion that always grab women's attention.